Un cavaller català a la cort de Niall Óg O'Neill, «princeps hibernicorum ultonie» (tardor del 1397). - PUIG, XAVIER RENEDO (Scripta)
Analysis of Ramon de Perellós' stay in Ireland during his pilgrimage to Saint Patrick's Purgatory: his route through the Isle of Man; the role of guides and Gaelic translators; the political situation in the island, half of which was controlled by the English king and the other half by the rebels; and finally, ways of life in rebel Ireland (nomadism, gastronomy, courtesy, etc.).